2016
DOI: 10.1139/cjas-2016-0032
|View full text |Cite
|
Sign up to set email alerts
|

A nutritional evaluation of common barley varieties grown for silage by beef and dairy producers in western Canada

Abstract: This study evaluated the nutritional and neutral detergent fiber digestibility (NDFD) characteristics of seven barley varieties (‘Conlon’, ‘CDC Copeland’, ‘CDC Cowboy’, ‘Falcon’, ‘Legacy’, ‘AC Metcalfe’, and ‘Xena’) grown for silage. Commercial samples (n = 80) harvested at the mid-dough stage were collected over 2 years (2012 and 2013). Average pH and dry matter (DM) content were 4.05% ± 0.17% and 36.8% ± 4.1%, respectively. ‘Falcon’ and ‘AC Metcalfe’ had higher (P < 0.05) CP relative to ‘CDC Copeland’ and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
31
2
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 26 publications
(37 citation statements)
references
References 55 publications
2
31
2
2
Order By: Relevance
“…silages, where CDC Cowboy BS had high NDF concentration, compared with other barley forages (55% vs. 50% DM). The fiber concentration for all barley varieties in the present study was greater than that reported by Nair et al (2016). The lower starch and higher NDF concentration for BS varieties in the present study may be attributed to effect of maturity and (or) environmental conditions that altered the chemical profile of the selected forages (Yu et al 2004).…”
Section: Resultscontrasting
confidence: 61%
See 4 more Smart Citations
“…silages, where CDC Cowboy BS had high NDF concentration, compared with other barley forages (55% vs. 50% DM). The fiber concentration for all barley varieties in the present study was greater than that reported by Nair et al (2016). The lower starch and higher NDF concentration for BS varieties in the present study may be attributed to effect of maturity and (or) environmental conditions that altered the chemical profile of the selected forages (Yu et al 2004).…”
Section: Resultscontrasting
confidence: 61%
“…Starch concentration was higher in CS (26.4% DM), intermediate for CDC Copeland and Xena BS (average 14.3% DM), and lower for CDC Cowboy BS (8.7% DM). A previous study by Nair et al (2016) reported a lower starch concentration for CDC Cowboy (14.7%), compared with CDC Copeland (21.0% DM) and Xena (20.0% DM). The fiber concentration differs between Table 2.…”
Section: Resultsmentioning
confidence: 71%
See 3 more Smart Citations